Investigasi Kemampuan Penalaran Siswa dalam Menyelesaikan Soal Matematika SMP Ditinjau dari Emotional Intelligence - Feby Fajriatur Rohmah; Soebagyo, Joko (Universitas Cokroaminoto Palopo, 2022)
In the process of solving problems, the different categories of Emotional Intelligence can affect the final results they get. The purpose of this study was to determine the process of students' reasoning abilities in solving junior high school math problems in terms of Emotional Intelligence. The research method used in this study is a qualitative research method with a case study approach. The subjects in this study were three junior high school students in South Tangerang. There are five indicators of mathematical reasoning ability in this study, namely collecting evidence, formulating conjectures, generalizing, justifying and drawing conclusions. Furthermore, the results of this study showed that subject T and subject S could cover all indicators of mathematical reasoning ability, namely indicators of collecting evidence, formulating conjectures, generalizing, justifying, and drawing conclusions. Meanwhile, subject R was able to meet the generalization and justifying indicators, but could not cover the indicators of collecting evidence, formulating conjectures and drawing conclusions.